THE IMPLEMENTATION OF PROBLEM BASED LEARNING WITH GALLERY WALK STRATEGY ON GLOBAL WARMING - AYU SEPTIANA, DILLA; SUNARTI, TITIN (Inovasi Pendidikan Fisika, 2019)
Higher order thinking skills (HOTS) is a high thinking skills that include critical thinking, logical, creative, reflective, and metacognitive. In 21st century, the corporate world becomes more competitive. Therefore, students require to have 21st century skills, 7C?s skill. For mastering those skills, students need HOTS. This research aims to analyse the implementation of problem based learning (PBL) with gallery walk strategy on global warming. The research method uses pre-experimental design with purposive sampling technique. The results shows that the mean score of 4 aspects includes: (1) the ability to open lessons, (2) implementation learning steps, (3) ability to close learning, and (4) class atmosphere in is implemented in category very well. Theoretically, the implementation of PBL with gallery walk strategy is able to enhance student?s HOTS. Keywords : Problem based learning, gallery walk strategy